Recurrent laryngeal nerve lymph node dissection may not be suitable for all early stage esophageal squamous cell carcinoma patients: an 8-year experience - Yu, Shaobin; Lin, Jihong; Chen, Chenshu; Lin, Jiangbo; Han, Ziyang; Lin, Wenwei; Kang, Mingqiang (Journal of Thoracic Disease, 2016)
Background: Recurrent laryngeal nerve (RLN) injury is one of the most frequent postoperative complications of esophageal squamous cell carcinoma (ESCC) radical resection. This study aims to develop a novel scoring system to predict recurrent laryngeal nerve lymph node (RLNLN) metastases in early ESCC and explore the indications for precise RLN lymphadenectomy. Methods: Early stage ESCC patients from 2006 to 2014 were analyzed. Patient and pathologic characteristics were compared between patients with RLNLN metastases and those without. Univariate and multivariate analyses were performed to establish a scoring system that estimates the risks of RLNLN metastases. The indications for RLNLN dissection were validated by survival rate, postoperative complications, and metastases rate. Results: A total of 311 cases selected from 1,466 ESCC patients were divided into the dissection group and the control group. Age, tumor length, macroscopic tumor type, T stage, tumor location and tumor differentiation were independent predictors of RLNLN metastases. The weighted scoring system included age (+2 for 4 points), 43.4%]. Besides, the dissection group had more complications and similar survival rate when compared with the control group. Conclusions: We developed a novel scoring system that accurately estimated the risk of RLNLN metastases in early ESCC patients. RLN lymphadenectomy may be safely omitted for the patients in the low-risk subgroup.